When happy people make society unhappy: How incidental emotions affect compliance behavior - Martin Fochmann; Frank Hechtner; Erich Kirchler; Peter N. C. Mohr (Arbeitskreis Quantitative Steuerlehre (arqus), 2019)
Emotions have a strong impact on our everyday life, including our mental health, sleep pattern, overall well-being, and judgment and decision making. Our paper is the first study to show that incidental emotions, i.e., emotions not related to the actual choice problem, influence the compliance behavior of individuals. In particular, we provide evidence that individuals have a lower willingness to comply with social norms after being primed with positive incidental emotions compared with aversive emotions. This result is replicated in a second study. As an extension to our first study, we add a neutral condition as a control. Willingness to comply in this condition ranges between the other two conditions. Importantly, this finding indicates that the valence of an emotion but not its arousal drives the influence on compliance behavior. Furthermore, we show that priming with incidental emotions is only effective if individuals are - at least to some extent - emotionally sensitive.
Keywords: C91; D91; H26; 330; compliance behavior; emotions; cheating; tax evasion; norms; experimental economics